The Contribution of Arrival Number of Halal Tourism and Economic Growth of West Sumatra Based on the Supply Chain Strategy: Using the Cointegration Test - Antoni Antoni; Ridzuan Masri; Abdul Murad Bin Ahmad; Reni Yuliviona; Ice Kamela; Irwan Muslim (International Journal of Supply Chain Management, 2019)
Abstract. The purpose of this research is to identify the relationship between the number of halal tourist arrivals of West Sumatra with economic growth by using the method of test and Granger cause testers Granger in the period 2000–2017. To review this written report, tourism growth is proxy with the number of tourist arrivals (LAR). While the economic consumption of income from tourism (LPAD) is utilized as a placeholder for the increase of tourism as the research. The significance of this research is the maturation of the tourism sector, which is more grievous in the hope it can contribute significantly to the economic and social development of the country in question. Further development in the tourism industry of West Sumatra as a tourist destination has put tourism industry, which knows the halal tourism industry as one of the important industry and the biggest contributor of the western Sumatra region.